2020
DOI: 10.1016/j.jhepr.2020.100154
|View full text |Cite
|
Sign up to set email alerts
|

Systemic iron reduction by venesection alters the gut microbiome in patients with haemochromatosis

Abstract: Venesection is the cornerstone of haemochromatosis treatment. Venesection leads to a compensatory increase in intestinal iron absorption. Reduced faecal iron availability leads to shifts in human colonic microbial composition. Changes in the human colonic metabolome occur with reduced faecal iron availability. Lay summary Iron depletion by repeated venesection is the mainstay of treatment for haemochromatosis, an ironoverload disorder. Venesection has been associated with several health benefits, including imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 19 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…Further research is viewed as unlikely to change the confidence in the estimate of the benefit and risk of venesection in this disease [ 63 ]. Consensus among experts exists that venesection is the first-line therapy for patients with hemochromatosis with similar proposals for how best to proceed [ 63 , 82 ]. As an example of qualification for venesection, patients should have a serum ferritin level >300 μg/L in men and >200 μg/L in women in combination with an elevated fasting transferrin saturation (>45%) for both men and women.…”
Section: Hemochromatosis Caused By Iron As a Toxic Elementmentioning
confidence: 99%
See 3 more Smart Citations
“…Further research is viewed as unlikely to change the confidence in the estimate of the benefit and risk of venesection in this disease [ 63 ]. Consensus among experts exists that venesection is the first-line therapy for patients with hemochromatosis with similar proposals for how best to proceed [ 63 , 82 ]. As an example of qualification for venesection, patients should have a serum ferritin level >300 μg/L in men and >200 μg/L in women in combination with an elevated fasting transferrin saturation (>45%) for both men and women.…”
Section: Hemochromatosis Caused By Iron As a Toxic Elementmentioning
confidence: 99%
“…As an example of qualification for venesection, patients should have a serum ferritin level >300 μg/L in men and >200 μg/L in women in combination with an elevated fasting transferrin saturation (>45%) for both men and women. Weekly or fortnightly venesection aims to achieve an initial serum ferritin target of 50–100 μg/L [ 82 ]. Each venesection typically removes 500 mL of blood, corresponding to 250 mg of iron [ 82 ].…”
Section: Hemochromatosis Caused By Iron As a Toxic Elementmentioning
confidence: 99%
See 2 more Smart Citations
“…As regular and adequate iron supply through diet is critical for both, intense competition for the metal prevails between the host and microbes. Numerous studies have shown that iron availability influences the gut microbiome composition and function [ 86 , 87 , 88 , 89 , 90 ]. Human studies representing various geographic and pathologic backgrounds show that modulation of dietary iron levels influences links gut microbiome with the etiopathogenesis of a variety of disorders like dysbiosis, inflammation, and colorectal cancer [ 91 , 92 , 93 , 94 ].…”
Section: Mammalian Ferritin and The Gut Microbiomementioning
confidence: 99%